1977
DOI: 10.1159/000162864
|View full text |Cite
|
Sign up to set email alerts
|

The Spontaneous Release of <sup>51</sup>Cr from Labeled EL-4 Ascitic Lymphoma Cells as Dependent Upon the Composition of the Cell Population

Abstract: Investigations on the spontaneous release of stCr from the EL-4 ascitic lymphoma showed that daily rhythmic changes can be correlated with the dominance of certain cell types in the population. A generation time of 9.8 h, an average doubling time of 32 h, and an ‘appearance cycle’ of 96 h were established for the population. Earlier observed variations in the values for spontaneous 51Cr release can be explained in terms of the cellular composition of the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1978
1978
1982
1982

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Lastly, our contention, presented in our previous publication [3], that considerable differences in immune lysis might result from variations in population composition, under otherwise identical experimental condi tions, has been borne out in the present study. A comparison of the final results of immune lysis, as compiled in table I, shows that the variation, depending upon the population rhythm, is from 13.5 to 52.5%, i.e., > 3 0 0 % .…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Lastly, our contention, presented in our previous publication [3], that considerable differences in immune lysis might result from variations in population composition, under otherwise identical experimental condi tions, has been borne out in the present study. A comparison of the final results of immune lysis, as compiled in table I, shows that the variation, depending upon the population rhythm, is from 13.5 to 52.5%, i.e., > 3 0 0 % .…”
Section: Discussionsupporting
confidence: 64%
“…On the other hand, when Q2 cells reenter the reproductive cycle, they will undergo mitosis once, giving rise to two indetermined early G, forms, thus increasing the proportion of vulnerable cells in compartment 1. In our previous study [3], it has been shown that compartments 3 and 4 (composed of D and Sn cells, respectively) are primarily responsible for the spontaneous release of 51Cr; therefore, it is not surprising that on days when these D and Sn cells dominate the population, immune lysis will be relatively slight, in comparison to those days when compartments 1 or 2 are in dominance.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Percent background release varied some what with each experiment possibly due to changes in cell cycle [9], Despite this varia- tion, the levels of background release for the attached labeled cells during a 24-hour incu bation period permitted its application in a long-term 24-hour assay for these tumor cell lines.…”
Section: Background Studiesmentioning
confidence: 99%